Revisiting the genus Diplodoma Zeller, 1852 in Europe: DNA barcoding reveals the presence of an undescribed species from forested habitats of southern Italy (Lepidoptera: Psychidae) - Cava, Sara La; Rijllo, Giuseppe; Zucco, Giada; Scalercio, Stefano (Zootaxa, 2025)
Diplodoma Zeller, 1852 is a Eurasian genus belonging to the family Psychidae Boisduval, 1829 of which three species are known in Europe: Diplodoma adspersella Heinmann, 1870, D. laichartingella (Goeze, 1783), and D. taurica Zagulajev, 1986. Some authors have argued that Diplodoma adspersella may be a subspecies or even a form of D. laichartingella. The revision of literature and the study of DNA barcoding fragments confirmed the inconsistency of D. adspersella as a valid species, and therefore we propose the new synonymy of Diplodoma adspersella with D. laichartingella (syn. nov.). During recent surveys in southern Italy, three specimens of Diplodoma were collected. DNA barcoding and morphological analyses showed that COI sequences and male genitalia significantly differ from any previously studied specimen. As a result, we described Diplodoma giulioregenii sp. nov., leaving unaltered the number of species belonging to this genus known from Europe.